Mortality and Cause of Death in Younger Homeless Veterans - Schinka, John A. (Public Health Rep, 2018)
OBJECTIVES: Increased mortality has been documented in older homeless veterans. This retrospective study examined mortality and cause of death in a cohort of young and middle-aged homeless veterans. METHODS: We examined US Department of Veterans Affairs records on homelessness and health care for 2000-2003 and identified 23 898 homeless living veterans and 65 198 non-homeless living veterans aged 30-54. We used National Death Index records to determine survival status. We compared survival rates and causes of death for the 2 groups during a 10-year follow-up period. RESULTS: A greater percentage of homeless veterans (3905/23 898, 16.3%) than non-homeless veterans (4143/65 198, 6.1%) died during the follow-up period, with a hazard ratio for risk of death of 2.9. The mean age at death (52.3 years) for homeless veterans was approximately 1 year younger than that of non-homeless veterans (53.2 years). Most deaths among homeless veterans (3431/3905, 87.9%) and non-homeless veterans (3725/4143, 89.9%) were attributed to 7 cause-of-death categories in the International Classification of Diseases, 10th Revision (cardiovascular system; neoplasm; external cause; digestive system; respiratory system; infectious disease; and endocrine, nutritional, and metabolic diseases). Death by violence was rare but was associated with a significantly higher risk among homeless veterans than among non-homeless veterans (suicide hazard ratio = 2.7; homicide hazard ratio = 7.6). CONCLUSIONS: Younger and middle-aged homeless veterans had higher mortality rates than those of their non-homeless veteran peers. Our results indicate that homelessness substantially increases mortality risk in veterans throughout the adult age range. Health assessment would be valuable for assessing the mortality risk among homeless veterans regardless of age.